Sequence–structure–function relationships of Tgs1, the yeast snRNA/snoRNA cap hypermethylase - Mouaikel, John (Oxford University Press, 2003)
The Saccharomyces cerevisiae Tgs1 methyltransferase (MTase) is responsible for conversion of the m(7)G caps of snRNAs and snoRNAs to a 2,2,7- trimethylguanosine structure. To learn more about the evolutionary origin of Tgs1 and to identify structural features required for its activity, we performed a structure–function study. By using sequence comparison and phylogenetic analysis, we found that Tgs1 shows strongest similarity to Mj0882, a protein related to a family comprised of bacterial rRNA:m(2)G MTases RsmC and RsmD. The structural information of Mj0882 was used to build a homology model of Tgs1p which allowed us to predict the range of the minimal globular MTase domain and the localization of other residues that may be important for enzyme function. To further characterize functional domains of Tgs1, mutants were constructed and tested for their effects on cell viability, subcellular localization and binding to the small nuclear ribonucleoproteins (snRNPs) and small nucleolar RNPs (snoRNPs). We found that the N-terminal domain of the hypermethylase is dispensable for binding to the common snRNPs and snoRNPs proteins but essential for correct nucleolar localization. Site- directed mutagenesis of Tgs1 allowed also the identification of the residues likely to be involved in the formation of the m7G-binding site and the catalytic center.